2012
DOI: 10.1103/physreva.85.013805
|View full text |Cite
|
Sign up to set email alerts
|

17 THz continuous-wave optical modulator

Abstract: We use coherently rotating hydrogen molecules and demonstrate a continuous-wave optical modulator at a frequency of 17.6 THz that can modulate any laser within the optical region of the spectrum. The molecules are coherently excited using two intense laser beams spaced by the Raman transition frequency inside a high-finesse cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Such modulators have recently achieved modulation rates approaching 100 GHz; yet, due to intrinsic limitations of electronic components, crystal-based approaches may remain unable to achieve much higher modulation rates. In contrast, we have recently demonstrated a modulator at a frequency of 17.6 THz using a rotational transition in molecular H 2 [30]. The experiment that we describe in this section extends our earlier result to a higher modulation rate of 90 THz by using a vibrational transition in molecular D 2 .…”
Section: Experiment: 90 Thz Cw Modulatormentioning
confidence: 35%
See 2 more Smart Citations
“…Such modulators have recently achieved modulation rates approaching 100 GHz; yet, due to intrinsic limitations of electronic components, crystal-based approaches may remain unable to achieve much higher modulation rates. In contrast, we have recently demonstrated a modulator at a frequency of 17.6 THz using a rotational transition in molecular H 2 [30]. The experiment that we describe in this section extends our earlier result to a higher modulation rate of 90 THz by using a vibrational transition in molecular D 2 .…”
Section: Experiment: 90 Thz Cw Modulatormentioning
confidence: 35%
“…It is important to note that, just as in the 90 THz mixing experiment described above, the cavity mirrors do not have a high reflectivity at the anti-Stokes wavelength, so the 807 nm beam is generated in a single pass through the system. We generate a maximum CW anti-Stokes power exceeding 1 mW, which is an order of magnitude larger than our previous experiments that relied on Raman lasing to generate the Stokes beam [30]. The predicted established molecular coherence in this experiment is more than an order of magnitude higher than what was achieved in the mixing experiment, |ρ ab | ≈ 1 × 10 −3 .…”
Section: Experiment: Preparing Molecules With Two Independent Cw Lasementioning
confidence: 83%
See 1 more Smart Citation
“…However, there are intrinsic difficulties in preparing the molecular coherence because of the relatively low intensities of cw lasers. A cw-MOM has been reported that used an optical cavity to enhance the intensities of the excitation beams [9], achieving MOM for a near-infrared cw laser with a efficiency greater than 10 −4 [10]. In these approaches, however, bulky optical cavities were used that might limit future applications that require robust, compact devices.…”
Section: Introductionmentioning
confidence: 99%
“…Carlsten and colleagues have laid the theoretical foundation for Raman gas-based CW lasers [14,15], and high-power Raman lasers in such systems have been constructed with H 2 or D 2 pressures ranging from 0.1 atm to 10 atm [16,17]. Cavity-based SRS with diatomic gas has also been proposed as a method for the construction of molecular modulators [18] for use in ultrashort pulse generation, and experimental progress has been made toward this goal as well [19,20].…”
Section: Introductionmentioning
confidence: 99%